(untitled) (Journal of Management and Social Sciences, 2024)
Being old comes with a lot of health crises that inhibit an aged person from adequately living a comfortable life as desired. However, advancement in medicine and technology is expected to make life comfortable for every human, particularly the ageing population. This paper relies on secondary data sourced from the internet to measure the health crises facing the ageing population. Evidence from the works of scholars showed that Nigeria has a very high, consistent, and rapid growth rate of the older population with serious health, social, economic and political implications. Findings revealed that old people without adequate care are often confronted with physical and psychological crises that eventually compound their socioeconomic and political lives. It is affirmed in this paper that maintaining a healthy state in old age is hampered by the onset of mental diseases, neurological disorders, drug use disorders and other health crises (diabetes, hearing loss and osteoarthritis). It is concluded that old age is crisis-driven and devastating to individuals and society. Thus, the paper recommends adequate medical and social support tailored to the specific need of individuals. Additionally, access to medical care should be tailored to the physical activity, occupation, education, and communication of the aged.